Um estudo da aplicação prática das grandezas de área e de volume e suas relações de proporção, aplicadas ao cotidiano do aluno - Schallenberger, Andréia (2017)
This research had as its theme the ideas suggested by the Trends in Mathematics Education and its applicability, highlighting the Ethnomathematics with its relations of the importance of the contextualization of the content and the Proportional Thinking that describes the way to think mathematically the daily relations, thus allowing a methodological support for the teaching of Area and Volume, through a practical activity. Through the bibliographic study, it was possible to verify a better understanding of these ideas and the relation of these with examples involving Mathematics and also Biology. We searched for information through a qualitative research in a second-year high school class at a public school, where the researcher is a teacher of Mathematics in the class. It was sought to know the students' previous knowledge about the content of Area and Volume and if they could apply them in an everyday situation. The questionnaire pointed out some important data about the difficulty of students in extending to a practical situation the elements involved in the content of Geometry. The proposal presented in this research reflects on an alternative for the teaching of the greatnesses that involves the content chosen, from the re-reading of a film, showing that methodology is not a form to be copied, but something that can be developed, from necessary fundamentals, improving pedagogical practice with certainty.